Identification of molecular targets for selective elimination of TRAIL-resistant leukemia cells. From spots to in vitro assays using TOP15 charts - Petrak, Jiri; Toman, Ondrej; Simonova, Tereza; Halada, Petr; Cmejla, Radek; Klener, Pavel; Zivny, Jan (Proteomics, 2009)
The resistance of malignant cells to chemotherapy calls for the development of novel anti-cancer drugs. TNF-related apoptosis-inducing ligand (TRAIL) is a pro-apoptotic cytokine, which selectively induces apoptosis in malignant cells. We derived two TRAIL-resistant HL-60 subclones, HL-60/P1 and HL-60/P2, from a TRAIL-sensitive HL-60 acute promyelocytic leukemia cell line. To identify therapeutically exploitable "weaknesses" of the TRAIL-resistant leukemia cells that could be used as molecular targets for their elimination, we performed proteomic (2-DE) analysis and compared both TRAIL-resistant subclones with the original TRAIL-sensitive HL-60 cells. We identified over 40 differentially expressed proteins. To significantly narrow the lists of candidate proteins, we excluded proteins that are known to be often differentially expressed, regardless of experiment type and tissue (the so-called "TOP15" proteins). Decreased expression of DNA replication and maintenance proteins MCM7 and RPA32 in HL-60/P1 cells, and the marked down-regulation of enzyme adenosine deaminase in HL-60/P2 cells, suggests increased sensitivity of these cells to DNA-interfering drugs, and adenosine and its homologues, respectively. In a series of in vitro assays, we confirmed the increased toxicity of etoposide and cisplatin to TRAIL resistant HL-60/P1 cells, and adenosine and vidarabine to HL-60/P2, compared with TRAIL-sensitive HL-60 cells.
Keywords: Gene Expression Regulation, Neoplastic; TNF-Related Apoptosis-Inducing Ligand; leukemie; protinádorové látky; HL-60 buňky; western blotting; 2D gelová elektroforéza; Minichromosome Maintenance Complex Component 7; regulace genové exprese u nádorů; protein TRAIL; replikační protein A; chemorezistence; Electrophoresis, Gel, Two-Dimensional; jaderné proteiny; DNA vazebné proteiny; proteiny buněčného cyklu; Blotting, Western; Leukemia; lidé; HL-60 Cells; Humans; MCM komplex, komponenta 7; apoptóza; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Drug Resistance, Neoplasm; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Cell Cycle Proteins; Nuclear Proteins; DNA-Binding Proteins; Apoptosis; Antineoplastic Agents; Replication Protein A